The risk of bleeding with warfarin: A systematic review and performance analysis of clinical prediction rules - Dahri, Karen; Loewen, Peter (Thrombosis and Haemostasis, 2007)
It was the objective of this article to qualitatively review and evaluate the clinical prediction rules (CPRs) available for estimating bleeding risk in patients commencing warfarin therapy. A systematic review of PubMed (1949 to December 2006), MEDLINE (1966 to December 2006); EMBASE (1980 to December 2006), Cochrane Database of Systematic Reviews (to December 2006), and International Pharmaceutical Abstracts (1970 to Demember 2006) was conducted. Seven studies were found that detailed CPRs used to assess risk of bleeding prior to commencing warfarin therapy. Four studies described distinct CPRs. The remaining three studies were further validations of one of the CPRs, the Outpatient Bleeding Risk Index. The Outpatient Bleeding Risk Index was classified as being of Level 2 evidence while the remaining three indices were classified as being of Level 4 evidence. In no case did the CPRs exhibit performance characteristics that would indicate“strong” ability to predict the presence of absence of major bleeding among warfarin recipients. The modified Outpatient Bleeding Risk Index exhibited moderate predictive ability for major bleeding in two studies, although pooling of all studies of this CPR did not reveal moderate or better performance. None of the CPRs identified “any bleeding” with moderate or strong predictive ability. None of the available CPRs exhibit sufficient predictive accuracy or have trials evaluating the impact of their use on patient outcomes. Hence, no existing CPR can be recommended for widespread use in practice at present.
Keywords: Bleeding risk; warfarin; clinical prediction rules